Aleopatia de fungos fitopatogênicos sobre plantas invasoras das culturas de soja e milho - Spiassi, Ariane (2011)
Invasive plants can cause problems to the exploitation of agriculture worldwide. The chemical control of these plants has generated several environmental problems, such as the contamination of natural resources, the compromising the food quality, the poisoning of farmers, the development of the weed s resistance, among others. An alternative to reduce the use of pesticides is the use of biological control, using pathogenic fungi that produce a variety of secondary compounds in culture medium, which exhibit phytotoxicity. Thus, the objective of this study was to determine the allelopathic activity of culture filtrate produced by pathogenic fungi that attack soybeans (Fusarium solani, Macrophomina phaseolina) and maize (Fusarium graminearum, Diplodia maydis). We evaluated the effects of fungal filtrates at concentrations of 0, 1, 5, 10, 15 and 20% on seed germination and on the developments of both radicle and hypocotyl of Canadian horseweed (Conyza canadensis (L.) Cronq.) broomstick (Bidens pilosa L.) and milkweed (Euphorbia heterophylla L.). Such effects were also tested on cultivated plants (soy and corn). The design of the experiment was completely randomized, with six treatments and four replications. The results indicate that the filtered solution of the Fusarium solani culture presented negative effect on Canadian horseweed, broomstick and milkweed without affecting the soy negatively. Diplodia maydis provided the reduction of growth of horseweed and milkweed without causing damage to the maize culture. Finally, the one of Macrophomina phaseolina decreased the growth of milkweed plantules without affecting the maize negatively, suggesting that these filtered solutions can be used for controlling invasive plants, being an ecologically friendly alternative for the reduction of the herbicides use and for protecting the environment